Goals and Tasks (Purpose) of Criminal Proceedings - K. A. Naumov (Сибирское юридическое обозрение, 2020)
The relevance of the problem covered is explained by the essence of goal-setting of any activity, which determines its final result and procedural structure. The direction of actions of state bodies in responding to crimes depends on it, as well as the arsenal of means provided for this to the law enforcement officer. The Criminal Procedure Code of the Russian Federation does not have a norm directly formulating the goal and objectives of criminal judicial proceedings. The legislator has applied such a non-standard category as “purpose”, which replaced the customary provisions that existed for more than 40 years on the tasks of criminal proceedings, enshrined in the previously existing code. Since the procedural law does not name the goals and objectives of the criminal process, the analysis of the target settings of modern criminal justice, the essence of the categories “purpose”, “goal”, “task”, their correlation and meaning is of particular importance. The Author analyzes the points of view of the processors of the pre-revolutionary and modern periods. The conclusion about the differentiation of the given concepts is made. Unlike the views of most scholars, the Author believes that purpose and goal are identical concepts, since they determine the final result of procedural activities. The goal is seen as the end result of the activity, and the task is determined by the goal and is considered as the result of its separate stage. Therefore, the Author conditionally correlates these categories as general (goal) and particular (task). There can be many tasks, and they are subject to changes under certain conditions, and the goal is always the same. The goal of any criminal process is determined by the need to streamline the dispute between the parties arising from the crime committed. The absence of clearly formulated elements of goal-setting prevents the assessment of the effectiveness of activities to resolve a criminal-legal conflict. The flaws in the legal structure of teleological norms of the current Criminal Procedure Code of the Russian Federation are noted. On the basis of a comparison of the views of procedural scholars, analysis of regulatory legal acts, the author came to the conclusion that the result of the criminal process should be the protection of the rights and legitimate interests of individuals, organizations, society and the state from criminal encroachments; protection of the individual from illegal and unjustified accusations, convictions, restrictions on his rights and freedoms. The tasks, despite their uncertainty from the point of view of legal regulation, constitute an established formula: quick and complete disclosure of a crime, the appointment of a just punishment to the guilty, education and prevention. The Author believes that the current structure of norms on the appointment of criminal proceedings does not reflect the absolute need to protect the interests of society and the state, and also does not define specific tasks as a guideline for the law enforcement officer to fulfill them in each criminal case in order to achieve this goal. Therefore, we propose our own legal structure of the norm on the tasks of legal proceedings, complementing the current provisions.